Enhancing Students' Biodiversity Literacy Through the Sundanese Ethnoscience-Based Discovery Learning Model - Nursalima, Irfan; Fitriani, Rita; Diella, Dea (Jurnal Pendidikan MIPA, 2025)
Biodiversity literacy encompasses students' understanding of biodiversity concepts, its utilization, and conservation efforts. This study aims to determine the effect of the ethnoscience-based discovery learning model on biodiversity literacy and students' scientific explanation skills in the classification of living organisms in Grade X at SMA Negeri 3 Tasikmalaya for the 2024/2025 academic year. The research method used was a quasi-experimental design. This study was conducted at SMA Negeri 3 Tasikmalaya during the 2024/2025 academic year, with the population consisting of 432 students from twelve classes in grade X. The sample was selected using purposive sampling, resulting in class X.E-1 as the experimental group and class X.E-2 as the control group. Data collection techniques included a biodiversity literacy test consisting of 33 multiple-choice questions. The result showed that the average score for biodiversity literacy in the experimental class was 75.85 (SD = 12.89), while in the control class, it was 65.15 (SD = 15.74). The ANCOVA analysis yielded a significance value of 0.006 (p < 0.05), indicating a statistically significant effect. Therefore, the result concludes that the Sundanese ethnoscience-based discovery learning model significantly influences biodiversity literacy in the classification of living organisms among Grade X students at SMA Negeri 3 Tasikmalaya.      Keywords: biodiversity literacy, discovery learning, ethnoscience, biology.